Patients either contacting a general practice cooperative or accident and emergency department out of hours: a comparison. Issue 9 (18th August 2006) - Giesen, P; Franssen, E; Mokkink, H; van den Bosch, W; van Vugt, A; Grol, R
Abstract : Introduction: Lack of collaboration between general practice (GP) cooperatives and accident and emergency (A&E) departments and many self referrals may lead to inefficient out-of-hours care. Methods: We retrospectively analysed the records of all patients contacting the GP cooperative and all patients self referring to the A&E department out of hours in a region in the Netherlands. Results: 258 patients contacted the GP cooperative and 43 self referred to the A&E department per 1000 patients per year. A wide range of problems were seen in the GP cooperative, mainly related to infections (26.2%). The A&E department had a smaller range of problems, mainly related to trauma (66.1%). Relatively few urgent problems were seen in the GP cooperative (4.6%) or for self referrals in the A&E department (6.1%). Women, children, the elderly, and rural patients chose the GP cooperative significantly more often, as did men and patients with less urgent complaints, infections, and heart and airway problems. Discussion: The contact frequency of self referrals to the A&E department is much lower than that at the GP cooperative. Care is complementary: the A&E department focuses on trauma while the GP cooperative deals with a wide range of problems. The self referrals concern mostly minor, non-urgent problems and can generally be treated by the general practitioner, by a nurse, or by advice over the telephone, particularly in the case of optimal collaboration in an integrated care facility of GP cooperatives and A&E departments with one access point to medical care for all patients.